2007
DOI: 10.1126/science.1144306
|View full text |Cite
|
Sign up to set email alerts
|

Blue-Light-Activated Histidine Kinases: Two-Component Sensors in Bacteria

Abstract: Histidine kinases, used for environmental sensing by bacterial two-component systems, are involved in regulation of bacterial gene expression, chemotaxis, phototaxis, and virulence. Flavin-containing domains function as light-sensory modules in plant and algal phototropins and in fungal blue-light receptors. We have discovered that the prokaryotes Brucella melitensis, Brucella abortus, Erythrobacter litoralis, and Pseudomonas syringae contain light-activated histidine kinases that bind a flavin chromophore and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
294
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(297 citation statements)
references
References 27 publications
(6 reference statements)
3
294
0
Order By: Relevance
“…In yet other studies, the role of HRXXN kinases in cellular processes other than the GSR has been demonstrated (44)(45)(46), although, at the same time, their involvement in the GSR has not been assessed, and thus cannot be excluded at this time. For example, in Rhizobium leguminosarum, the orphan HRXXN kinase R-LOV-HK (pLR110320) regulates light-dependent cell attachment, exopolysaccharide production, and nodulation, but the response regulator presumably mediating this response was not identified and the involvement of PhyR in these phenotypes has not been studied (44).…”
Section: Discussionmentioning
confidence: 99%
“…In yet other studies, the role of HRXXN kinases in cellular processes other than the GSR has been demonstrated (44)(45)(46), although, at the same time, their involvement in the GSR has not been assessed, and thus cannot be excluded at this time. For example, in Rhizobium leguminosarum, the orphan HRXXN kinase R-LOV-HK (pLR110320) regulates light-dependent cell attachment, exopolysaccharide production, and nodulation, but the response regulator presumably mediating this response was not identified and the involvement of PhyR in these phenotypes has not been studied (44).…”
Section: Discussionmentioning
confidence: 99%
“…Their diverse properties make flavins of paramount importance for many biological systems. [1][2][3][4][5][6] For instance, flavins absorb in a wide spectral range from the optical up to the UV region, and their absorption maxima vary sensitively with structural modifications. In this way, flavincontaining domains act as light-harvesting modules in plants and algal phototropins and as blue-light receptors in fungals.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, flavincontaining domains act as light-harvesting modules in plants and algal phototropins and as blue-light receptors in fungals. 5 Furthermore, as an important component of flavoproteins they are involved in the repair of DNA, 7 serve as cofactor in the enzyme GOx which oxidizes glucose to hydrogen peroxide, and are involved in the redox cycle of the respiratory chain by acting as an electron donor and acceptor. 6 Their broad (bio-)chemical activity is based on the existence of three different oxidation states, namely, the oxidized state (flavoquinone), the singly reduced or radical state (flavosemiquinone), and the fully reduced state (flavohydroquinone).…”
Section: Introductionmentioning
confidence: 99%
“…As two of the world's largest beef exporters, Argentina and its neighbour Brazil together lose an estimated $100 million annually to the disease. Last year, working with Roberto Bogomolni of the University of California, Santa Cruz, Goldbaum identified light-sensitive proteins that increase the virulence of brucellosis bacteria 3 .…”
Section: Anonymous Donorsmentioning
confidence: 99%